Analisis Kepuasan Pengguna Menggunakan Kombinasi End User Computing Satisfaction Dan Servqual Pada Website KEMENAG Provinsi Maluku - Nalbraint Wattimena; Kristoko Dwi Hartomo; Hendry Hong (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
In recent years, the need for online service information has been increasing. To meet this need, the Regional Office of the Ministry of Religious Affairs in Maluku Province, through religious institutions, provides service information on their website using information system technology. In the last three months, total visits to the Ministry's website have increased by 39.4%. However, there are still issues with the website, such as complicated and time-consuming navigation due to large and numerous menu displays. A user satisfaction survey for this website has also never been conducted. Due to these issues, the researchers are interested in studying user satisfaction with the Ministry of Religious Affairs website using a combination of the EUCS and Servqual methods. This study aims to obtain an in-depth understanding of user satisfaction with the website using these combined methods and to identify various factors influencing user satisfaction. The results indicate that 8 variables have very high satisfaction values. From the T-test conducted, 7 variables affect user satisfaction: accuracy, format, ease of use, timeliness, responsiveness, assurance, and empathy. Among these, the most influential variable is format. Meanwhile, one variable, content, does not affect user satisfaction. According to the F-test results, the variables content, accuracy, format, ease of use, timeliness, responsiveness, assurance, and empathy collectively influence user satisfaction.